Simple and efficient method to fabricate nano cone arrays by FIB milling demonstrated on planar substrates and on protruded structures - Rommel, Mathias; Bauer, A. J.; Frey, Lothar (Microelectronic Engineering, 2012)
A simple, fast and efficient method is demonstrated for the fabrication of very homogeneous periodic nano-cone arrays on planar Si substrates by focused ion beam milling. The approach makes use of the actual shape of the ion beam by simply milling lines in vertical and horizontal direction with the lines separated by the targeted periodicity. If beam currents and, thus, beam diameters are chosen appropriately, this patterning approach results in nano-cone arrays with apex radii of 25 nm and below. Arrays with periodicities of 600, 300, and 150 nm are realized with minimum processing times of the order of 30 s for an area of 30 extgreekmm2 without a change in the quality of the cones by area scaling. To a certain extent, height, aspect ratio, apex radius and shape of the individual cones can be varied using different beam diameters. While constant dwell times are used for planar samples, it is shown that homogeneous nano-cone arrays can only be realized on the whole surface of protruded rectangular mesa structures if the patterning strategy is adapted appropriately. In the successfully modified approach the dwell time is gradually decreased along the milled lines from the center of the array towards the edges and a frame like pattern is added at the edges of the protruded structures.
Keywords: FIB; FIB patterning; Focused ion beam; Nano cone array; Patterning strategy; Tip array